Non-cell-autonomous induction of tissue overgrowth by JNK/Ras cooperation in a Drosophila tumor model - Uhlirova, Mirka (National Academy of Sciences, 2005)
The role of c-Jun N-terminal kinase (JNK) signaling in cancer is enigmatic, and both tumor-promoting and tumor-suppressing functions have been ascribed to JNK pathway components. We have used the Drosophila eye to investigate the function of the JNK pathway in three different tumor models of increasing malignancy. Benign lesions caused by loss of the neoplastic tumor suppressor gene scribble can efficiently be eliminated by JNK-induced apoptosis. In such a scenario, the eye reverts to a wild-type phenotype, indicating that the JNK pathway prevents tumor formation. The situation changes in the case of aggressive tissue overgrowth, which can be induced by oncogenic activation of the Ras/Raf pathway in the eye, or in malignant invasive tumors resulting when Raf activation is combined with loss of scribble. The growth of these more aggressive tumor types is significantly, yet incompletely, suppressed by JNK-mediated apoptosis. Remarkably, oncogenic Raf and JNK cooperate in these tumors, to induce massive hyperplasia in adjacent wild-type tissue. Thus, depending on the genetic context, JNK signaling can eradicate tumors by removing premalignant cells, or promote aberrant overgrowth in tissues surrounding primary lesions.